Group Formation of the Long-Tailed Macaques Introduced onto Tinjil Island, West Java - Entang Iskandar; Randall C Kyes; Rondang Siregar; R.P Agus Lelana (Department of Forest Resources Conservation and Ecotourism - IPB University, 1996)
Between 1;ebruary 1488 and June 1941, 478 long-tailed macaques (58 males, 420 females) were releasedonto 'Tinjil Island to estahlisli a natural habitat breeding facility. The monkeys were released on 10 differentoccasions over the three years period and did not represent established social groups at the time of release. Approxirnalely 33% of the entire breeder populalion (28 males and 130 females) has been identified by tattoo. Because each monkey received a chest tattoo before released onto the island, it has been possible to reconstruct and tract social group formation by matching an individual's tattoo with its date of release. Assesment of the tattoo data From five of the groups identified on the island indicates that the social groups are not composed of animals from a single release group, hut rather consist of animals from several release groups. Animals from all10 release groups are represented among the five social groups. Membership in the five groups has remainedrelatively stahle during the past four years olohservation (1990-1993) with minimal exchange of group members.